Bone Injury and Fracture Healing Biology - Oryan, Ahmad; Monazzah, Somayeh; Bigham-Sadegh, Amin (Biomedical and environmental sciences, 2015)
Bones are organs of the skeletal system, providing shape, mechanical support, and protection to the body and facilitating the movement. In addition, bones contribute to the mineral homeostasis of the body and have recently been found to participate in endocrine regulation of energy metabolism. The well-known limitations associated with clinical use of autografts and allografts continue to drive efforts to develop bone graft substitutes, using the principles of biomaterials and tissue engineering. Under some stressful and continuous compressive conditions, the ability of the bone tissue to tolerate strength decreases. Whenever these forces overcome the toleration of the bone tissue, bone fracture occurs. years